Semiconductor materials for x-ray detectors. (9th June 2017) - Pennicard, David; Pirard, Benoît; Tolbanov, Oleg; Iniewski, Krzysztof
Abstract: Abstract : Semiconductor x-ray detectors are widely used in experiments at synchrotron facilities. The performance of these detectors depends heavily on the semiconductor material properties. Improvements in crystal growth and device processing are key to developing "high- Z " (high atomic number) semiconductors for hard x-ray detection. Germanium is the most mature high- Z semiconductor and is widely used in x-ray detectors, but it has the drawback of needing to be cooled during operation, often to cryogenic temperatures. Compound semiconductors with wide bandgaps can be used at room temperature, but crystal defects can degrade their performance. Gallium arsenide currently shows poorer energy resolution, but its comparative robustness and stability over time make it a strong option for imaging detectors. Cadmium telluride and cadmium zinc telluride both provide higher detection efficiencies at extreme x-ray energies as well as good energy resolution; the main challenge with these materials is maintaining consistent behavior under a high x-ray flux.